Kesehatan Mental Dalam Islam - Yudha Hafidh Pratama; Ahmad Raihan Anargya; Athila Shofia Rosidah (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Mental health is a vital aspect of deep human life, and religious views play a crucial role in understanding it. This research aims to explore and understand the relationship between mental health and religious perspectives on individual quality of life. The research method used was a systematic review by searching for articles on Google Scholar using the keywords "Health," "Mental," "Al-Qur'an," and "Islam." Inclusion criteria include research articles in the last 10 years, Indonesian, in journal form, and publicly accessible. The research results show that mental health plays an important role in the Islamic view, which provides comprehensive guidelines for maintaining mental health. In the Islamic view, several important aspects include tawakkal (submission of oneself to Allah), dhikr and prayer to relieve stress and anxiety, maintaining balance in life, supporting healthy social relationships, providing social support, forgiveness, patience, and when needed, seeking help professionals such as psychotherapy or counseling. The Islamic view of mental health involves spiritual, psychological, and social dimensions, and by combining religious teachings with appropriate medical care and social support, individuals can achieve optimal mental health in accordance with the principles of their religion. Mental health in the Islamic view is an integral component of efforts to achieve holistic well-being in an individual's life.